Workload Analysis Turnover Intention With Work Life Balance and Burnout as a Variable Intervening at PT. Merak Jaya Beton - Rachmayanti, Difa; Fauzi, Akhmad (PT FORMOSA CENDEKIA GLOBAL, 2024)
Human resources are the main important factor in a company. One of the problems that affects the workforce in a company is level turnover. High level turnover intention has become a problem that has a negative impact on the company. That's why it's important for companies to pay attention to employee welfare, such as workload. Each individual has different resistance to workload, the higher the workload given, the higher the level turnover intention. Besides that Work life balance The company also needs to pay attention. the higher the quality work life balance employees then the lower the level turnover intention employees or even none at all. Burnout It should also be noted that work burnout can be the main consideration for employees who experience a high workload turnover intention.